TASAWUF SUNNI ALA SIRHINDI: â€œKAWIN PAKSAâ€ MONISME DAN TEOLOGI ASYâ€™ARIYAH - Labib, Muhsin (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2012)
The term monism or wahdah al-wujūd has a long story in Islamic Mysticism or Sufism. It is such that is considered to be the soul of Sufism, an sich. It means that without wahdah al-wujūd, there would be no further discussion on Islamic Mysticism. Besides, the theory of wahdah al-wujūd is rooted in Shi’ite Islam, yet never found in the Theology of Ash’arian or any other Sunni tradition. It is very important to have an awareness of what the author has termed ‘failed cloning’ between monism in Shi’ite and dualism in Sunni traditions established by Sirhindi. This is an attempt to uncover the weakness and/or weaknesses of Sirhindi’s methodology, that criticized wahdah al-wujūd and his subsequent misunderstanding of it. Moreover, Sirhindi seemed somewhat confused over the disciplines of mysticism, philosophy, theology and jurisprudence in his arguments and accordingly his mystical construction. To criticize wahdah al-wujūd without having a basic understanding of Ibn ‘Arabi’s works is a fault. Moreover, the construction of mystical dimension of wahdah al-wujūd of Ibn ‘Arabi which had staunchly strengthened and defended by Shadruddin Shirazi (Mulla Sadra) is very difficult to break through by anyone who does not have basic knowledge of either. Thus, Sirhindi should have learned from him (Mulla Sadra) before he criticized Ibn ‘Arabi and his concept wahdah al-wujūd